FEASIBILITY ANALYSIS OF CARP (Cyprinuscarpio) FARMING AND MARKETING IN DELI SERDANG DISTRICT - Zul Fadhly; Retna Astuti Kuswardani; Endang Sari Simanullang (CV. Radja Publika, 2024)
The aim of this research isto analyze the income of carp farmers(Cyprinus carpio)in Deli Serdang Regency and Simalungun Regency, to analyze the comparative feasibility of goldfish farming(Cyprinus carpio)between Deli Serdang Regency and Simalungun Regency.The sampling technique in this research was carried out using provocative sampling with categories: privately owned land, land area 1.5-2 ha. to 20 farmers each. Financial analysis methods, feasibility analysis, analysis and efficient analysis with analysis of business costs, revenues and profits, break even point (BEP), R/C Ratio, B/C Ratio. The research results show that: Profits in Deliserdang Regency are averageRp.9,024,492 per harvest The marketing efficiency of carp farming in Deliserdang Regency is an average of 9.73%, so marketing is efficient.